Platypus helping deliver the future - TKI Medcon Inc. (Ottawa, Ont. : TKI Medcon, 1999)
Platypus is the most extensive multimedia, prenatal ultrasound reference tool available. This interactive software provides easy, quick access to all current anatomical systems and procedures
System requirements : Windows ; Pentium 120MHz or greater, Windows 95, 98 or Windows NT, Video resolution of 800 x 600 in Hi-color (16 bit), Sound card, SVGA Monitor
System requirements : Macintosh and PowerPC ; 68040 or greater, Mac OS 7.5.1 or greater, Video resolution of 800 x 600 in thousands of colors, Sound card, SVGA Monitor
Keywords: Fetus -- Abnormalities; Abnormalities -- ultrasonography; Ultrasonography, Prenatal